Über Grenzverteilung eines Funktionals von unabhängigen Zufallsgrößen - Survila, P. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:П. Сурвила. О предельном распределении одного функционала от последовательности независимых случайных величинP. Survila. Apie nepriklausomų atsitiktinių dydžių vieno funkcionalo ribinį pasiskirstymą